Revision of Lithosia Fabricius, 1798 and Conilepia Hampson, 1900 (Lepidoptera, Arctiidae) - Dubatolov, Vladimir V.; Zolotuhin, Vadim V.; Witt, Thomas J. (Zootaxa, 2016)
This paper deals with the revision of the Arctiidae genera Lithosia Fabricius, 1798 and Conilepia Hampson, 1900. Only two species currently are considered to be members of Lithosia, Lithosia quadra Linnaeus, 1758, and Lithosia yuennanensis Daniel, 1952. It is here proposed to consider the Far-Eastern populations of L. quadra as subspecies Lithosia quadra dives Butler, 1877, stat. rev. and the Transcaspian populations of the species are described here as Lithosia quadra ssp. soligena ssp. nov. The lectotype of Phalaena Noctua deplana Linnaeus, 1771, preserved in the Hunterian Museum of London, is designated. Two species, Lithosia subcosteola Druce, 1899 and Lithosia gynaegrapha de Joannis, 1930, are excluded from Lithosia. The rare and local Lithosia quadra sikkima Strand, 1922 is raised to species rank and transferred to Conilepia, comb. et stat. nov. The male of C. sikkima is described for the first time. Three species are considered to belong to the genus Conilepia, among them Conilepia cao sp. nov., which is described from Vietnam. All taxa are described and figured. A scenario for the faunogenesis of the Lithosia-Conilepia complex is proposed using molecular data.